The Effect of The Make A Match Model Assisted with Question Answer Card in The Excretion System Material on Students’ Motivation and Cognitive Learning Outcomes (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
The purpose of this study was to determine the effect of the model make a match assisted by question answer card on the excretion system on students' motivation and cognitive learning outcomes. The design of this study is Nonequivalent Control Group Design. The population of this research are students of class VIII semester 2, SMP N 1 Karangsambung, Kebumen. The samples to be used are class VIII A (experimental class) and VIII B (control class). Sampling technique with cluster random sampling. Analysis of the data used by the n-gain test and t test. This study has the results that there is an influence of make a match model assisted by the question answer card on the motivation and cognitive learning outcomes of students. The effect can be seen from the results of an increase test using N-Gain, the results obtained from the data that there is an increase in students' cognitive learning outcomes. Based on the results of this study